2018
DOI: 10.1103/physrevb.97.214512
|View full text |Cite
|
Sign up to set email alerts
|

Formation of single-phase disordered CsxFe2ySe2

Abstract: A single-phase high pressure (HP) modification of CsxFe2-ySe2 was synthesized at 11.8 GPa at ambient temperature. Structurally this polymorph is similar to the minor low pressure (LP) superconducting phase, namely they both crystallize in a ThCr2Si2-type structure without ordering of the Fe vacancies within the Fe-deficient FeSe4 layers. The HP CsxFe2-ySe2 polymorph is found to be less crystalline and nearly twice as soft compared to the parent major and minor phases of CsxFe2-ySe2. It can be quenched to low p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Despite the observation of phase separation in A 1−x Fe 2 Se 2 , the transport, magnetization, and heat capacity studies confirmed 100% Meissner shielding in these materials, which seems a bit controversial in the context of a phase separation phenomenon evidenced so far by neutron diffraction (Yu Pomjakushin et al, 2012;Zhao et al, 2012), x-ray diffraction and spectroscopy studies (Ricci et al, 2011;Bosak et al, 2012;Svitlyk et al, 2018), muon spin rotation spectroscopy (Charnukha et al, 2012;Shermadini et al, 2012), NMR (Torchetti et al, 2011;Texier et al, 2012), scanning electron microscopy (SEM) (Speller et al, 2012(Speller et al, , 2014, scanning tunneling microscopy (STM) (Ding et al, 2013), and magnetic force microscopy (MFM) imaging (Hazi et al, 2018;Dudin et al, 2019). After nearly a decade of research on the origin of phase separation phenomena, there is a general agreement that the vacancy-free A 1−x Fe 2 Se 2 superconducting phase forms only in the presence of an insulating vacancyordered antiferromagnetic majority phase with the chemical composition close to A 0.8 Fe 1.6 Se 2 (Speller et al, 2012;Carr et al, 2014;Bao, 2015) while the superconducting one is a metallic vacancy-free phase.…”
Section: Intercalated Iron Selenide-the Influence Of the Chemical And Electrochemical Nature Of Intercalating Species On The Crystal Strumentioning
confidence: 92%
See 2 more Smart Citations
“…Despite the observation of phase separation in A 1−x Fe 2 Se 2 , the transport, magnetization, and heat capacity studies confirmed 100% Meissner shielding in these materials, which seems a bit controversial in the context of a phase separation phenomenon evidenced so far by neutron diffraction (Yu Pomjakushin et al, 2012;Zhao et al, 2012), x-ray diffraction and spectroscopy studies (Ricci et al, 2011;Bosak et al, 2012;Svitlyk et al, 2018), muon spin rotation spectroscopy (Charnukha et al, 2012;Shermadini et al, 2012), NMR (Torchetti et al, 2011;Texier et al, 2012), scanning electron microscopy (SEM) (Speller et al, 2012(Speller et al, , 2014, scanning tunneling microscopy (STM) (Ding et al, 2013), and magnetic force microscopy (MFM) imaging (Hazi et al, 2018;Dudin et al, 2019). After nearly a decade of research on the origin of phase separation phenomena, there is a general agreement that the vacancy-free A 1−x Fe 2 Se 2 superconducting phase forms only in the presence of an insulating vacancyordered antiferromagnetic majority phase with the chemical composition close to A 0.8 Fe 1.6 Se 2 (Speller et al, 2012;Carr et al, 2014;Bao, 2015) while the superconducting one is a metallic vacancy-free phase.…”
Section: Intercalated Iron Selenide-the Influence Of the Chemical And Electrochemical Nature Of Intercalating Species On The Crystal Strumentioning
confidence: 92%
“…After nearly a decade of research on the origin of phase separation phenomena, there is a general agreement that the vacancy-free A 1−x Fe 2 Se 2 superconducting phase forms only in the presence of an insulating vacancyordered antiferromagnetic majority phase with the chemical composition close to A 0.8 Fe 1.6 Se 2 (Speller et al, 2012;Carr et al, 2014;Bao, 2015) while the superconducting one is a metallic vacancy-free phase. There were also several structural models suggested for both these phases involving the different ordering of iron and alkali metal vacancies, specific ordering of charges and spins, and magnetic domains orientation (Li et al, 2012;Ding et al, 2013;Carr et al, 2014;Svitlyk et al, 2018), but until today any consistent model covering all the experimental observables has not been proposed. It has been experimentally proved that tiny domains of the minority phase are uniformly distributed in the AFM-ordered majority A 0.8 Fe 1.6 Se 2 phase, forming a specific percolation network throughout the whole macroscopic crystallite, enabling high Meissner screening.…”
Section: Intercalated Iron Selenide-the Influence Of the Chemical And Electrochemical Nature Of Intercalating Species On The Crystal Strumentioning
confidence: 99%
See 1 more Smart Citation